2017
DOI: 10.1186/s40360-017-0181-2
|View full text |Cite
|
Sign up to set email alerts
|

Frequency, characteristics and risk factors of QT interval prolonging drugs and drug-drug interactions in cancer patients: a multicenter study

Abstract: BackgroundCancer patients may receive a high number of medications with the potential to prolong QT interval and subsequent TdP (torsades de pointes). This study aimed to identify the prevalence of QT prolonging drugs, their TdP risk, QT prolonging drug-drug interactions (QT-DDIs), levels, predictors, and TdP risk of drugs involved in QT-DDIs.MethodsThis multicenter study included cancer patients from three major tertiary care hospitals of Khyber-Pakhtunkhwa, Pakistan. Micromedex DrugReax® was used for identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 27 publications
(28 reference statements)
0
23
1
2
Order By: Relevance
“…Among the detected drug interactions that need be taken into account is ciprofloxacin and metronidazole; these drugs cause QT prolongation and their concurrent use increases the risk of this side effect, and so attention should be given to such interaction [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the detected drug interactions that need be taken into account is ciprofloxacin and metronidazole; these drugs cause QT prolongation and their concurrent use increases the risk of this side effect, and so attention should be given to such interaction [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in special populations such as cancer patients there is increased risk of drug interactions resulting in QTc prolongation. For example, greater prevalence is associated with breast and gastrointestinal cancer diagnoses as well as solid-based malignancy [59]. Finally, TdP may be influenced by an individual’s repolarization reserve [60], which is genetically determined and involves compensatory mechanisms that modulate unfavorable changes in depolarizing or repolarizing currents which may contribute to arrhythmogenesis.…”
Section: Long Qtc Syndromes (Lqts)mentioning
confidence: 99%
“…In a cross-sectional retrospective study of 555 patients with cancer, 92.6% of patients received QTc-prolonging drugs, mostly commonly antiemetic agents, proton pump inhibitors, and antimicrobial agents, and 21.8% received medications involved in QTc-prolonging drugedrug interactions. 34 Furthermore, a systematic review of patients receiving conventional cancer treatment reported a QTc prolongation incidence of between 0% and 22%. 35 The present study included a large number of patients with HR+/HER2-mBC (24,340 women) and assessed several risk factors for QTc prolongation, including concomitant medication use, cardiovascular disease, electrolyte abnormalities, and congenital long QT syndrome.…”
Section: Risk Factormentioning
confidence: 99%